A fast method for analyzing essential protein mutants in human cells. (February 2017) - Dietsch, Frank; Donzeau, Mariel; Cordonnier, Agnes M.; Weiss, Etienne; Chatton, Bruno; Vigneron, Marc
Here we developed a complementation method for the study of essential genes in live human cells using the CRISPR/Cas9 system. Proteins encoded by essential genes were expressed using a derivative of the pCEP4 compensating plasmid in combination with Cas9 endonuclease targeting of the chromosomal genes. We show that this strategy can be applied to essential genes, such as those coding for proliferating cell nuclear antigen ( PCNA ) and DNA polymerase delta subunit 2 ( POLD2 ). As demonstrated for the PCNA protein, our method allows mutational analysis of essential protein-coding sequences in live cells.